Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/ncomms13853
|View full text |Cite
|
Sign up to set email alerts
|

PKCɛ switches Aurora B specificity to exit the abscission checkpoint

Abstract: The ‘NoCut', or Aurora B abscission checkpoint can be activated if DNA is retained in the cleavage furrow after completion of anaphase. Checkpoint failure leads to incomplete abscission and a binucleate outcome. These phenotypes are also observed after loss of PKCɛ in transformed cell models. Here we show that PKCɛ directly modulates the Aurora B-dependent abscission checkpoint by phosphorylating Aurora B at S227. This phosphorylation invokes a switch in Aurora B specificity, with increased phosphorylation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Here, we identify RIF1 and its binding partner, protein phosphatase 1 (PP1), as being critical for regulation of abscission timing in human cells. We show that RIF1 promotes cytokinesis through recruitment of PP1 to the midbody, which then counteracts Aurora B kinase activity, leading to dephosphorylation of a regulator of abscission timing, CHMP4C [6][7][8][9][10]. Although RIF1 binds to unresolved DNA bridges that persist into telophase [11], we show that this cytokinetic function of the RIF1-PP1 axis is not limited to instances where cell division is perturbed by the presence of bridges.…”
Section: Discussionmentioning
confidence: 89%
“…Here, we identify RIF1 and its binding partner, protein phosphatase 1 (PP1), as being critical for regulation of abscission timing in human cells. We show that RIF1 promotes cytokinesis through recruitment of PP1 to the midbody, which then counteracts Aurora B kinase activity, leading to dephosphorylation of a regulator of abscission timing, CHMP4C [6][7][8][9][10]. Although RIF1 binds to unresolved DNA bridges that persist into telophase [11], we show that this cytokinetic function of the RIF1-PP1 axis is not limited to instances where cell division is perturbed by the presence of bridges.…”
Section: Discussionmentioning
confidence: 89%
“…PKCε phosphorylates AURKB at Ser227 which alters the substrate selectivity of AURKB towards a particular set of substrates, and this switch is essential for the completion of cell division after the abscission checkpoint 32 . AURKB Ser227 is equivalent to AURKC Ser193 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…INCENPb becomes chronologically critical for the localization and activity of Aurora B on the central spindle and midbody. A comparative proteomics analysis has shown that Aurora B dramatically switches its binding partners in the mitosis to cytokinesis transition, with many involved in microtubule binding and cytoskeleton organization [52,53]. Intermediate filaments such as vimentin, GRAP (glial fibrillary acidic protein) and desmin are components of intercellular bridges, and phosphorylation by Aurora B can lead to their disassembly [54].…”
Section: Incenpb Is Critical For the Localization And Activity Of Aurmentioning
confidence: 99%